GEOCHEMISTRY AND ORIGIN OF GAS POOLS IN THE GAOQING-PINGNAN FAULT ZONE, JIYANG DEPRESSION - Shen B.; Huang Zh.; Liu H.; Xu Ch.; Yan Z.; Chen M. (My University, 2007)
In the surroundings of the Gaoqing-Pingnan fault zone are developed quite a number of gas reservoirs. Based on gas compositions, they can be divided into two groups, i.e., CO2 and CH4. Their composition and isotope geochemistry were dealt with in this study. The CO2 contents range from 60.72%–99.99%, the δ13 $C_{CO_2 } $ values from −3.41‰–−9.8‰, and the 3He/4He ratios from 4.35×10−6−6.35×10−6 (i.e. R/Ra=4.45–4.35). Based on the data on composition and isotope geochemistry, deep geological background, deep faults and volcanic rocks, it is shown that CO2, distributed in the Gaoqing area, mostly originated from mantle-source inorganic matter which is associated with magmatic rocks. The favorable tectonic environment for the formation of CO2 reservoirs is the rift, which is related to great fault-magmatic activity, the formation of CO2 gas pools and their space-time correlation to the most recent magmatic activities. Hydrocarbon gas pools occur in the Huagou area. The CH4 contents are within the range of 88.83%–99.12%, and the δ13 $C_{CH_4 } $ values, −44.7‰–−54.39‰ This indicates that the hydrocarbon gas resulted from the decomposition of oil-type gas at high temperatures. Volcanic rocks in the CO2 gas pool-and CH4 gas pool-distributed areas show significant differences in Fe2O3 and FeO contents. This has proven that the hydrocarbon gas may have resulted from various chemical reactions. Magmatic activities are the primary reason for the distribution of CO2 and CH4 gas pools in the Gaoqing-Pingnan fault zone.
Keywords: GAS POOL; GEOCHEMISTRY; MAGMATIC ACTIVITY; MANTLE ORIGIN; JIYANG DEPRESSION